Association between the atherogenic index of plasma and mortality in the chronic kidney disease population: evidence from NHANES - Li, Luohua; Zhao, Jinhan; Yuan, Mei; Jiang, Hongying (Frontiers in Medicine, 2025)
BackgroundThe atherosclerosis index (AIP) in plasma is a novel indicator closely associated with various metabolic abnormalities, and the bidirectional relationship between metabolic dysfunction and chronic kidney disease (CKD) has been extensively documented. However, evidence regarding the association between AIP and mortality in CKD population remains scarce. This study aims to elucidate the association between baseline AIP levels and both all-cause and specific mortality in a diverse cohort of US adults.MethodsThis cohort study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning from 1999 to 2018. A total of 4,403 participants were included in the analysis. Mortality rates were determined through linkage with the National Death Index (NDI), with follow-up extending through December 31, 2019. The primary outcome variables were all-cause mortality and cause-specific mortality. Multivariable weighted Cox proportional hazards regression models, restricted cubic spline analysis, subgroup stratification, and sensitivity testing were utilized to evaluate the associations between the AIP and both all-cause and cause-specific mortality.ResultsDuring a median follow-up of 83 months, 1,767 all-cause deaths and 526 CVD deaths occurred. After multivariable adjustment, AIP was independently associated with elevated risks of all-cause mortality (HR: 2.03, 95% CI: 1.62∼2.55, P < 0.001) and cardiovascular mortality (SHR: 1.60, 95% CI: 1.08∼2.39, P = 0.028). Restricted cubic spline analysis confirmed a linear dose-response relationship between AIP and all-cause mortality (P for non-linearity = 0.243). Subgroup analyses confirmed consistent associations across demographics and comorbidities, with significant interactions observed for sex, BMI, and diabetes (P < 0.05). Sensitivity analyses excluding deaths within 2 years showed similar outcomes (all-cause mortality HR: 1.94, 95% CI: 1.53∼2.47, P < 0.001; CVD mortality SHR: 1.69, 95% CI: 1.13∼2.53, P = 0.01).ConclusionData from large cohort studies have revealed a significant positive correlation between AIP levels and the risks of all-cause and cardiovascular mortality in the adult population of the United States. This suggests that AIP is associated with an increased risk of adverse outcomes in CKD and may serve as biomarker.